Crust material with cross-linked network structure as well as preparation method and application thereof
By developing a crust material with a crosslinked network structure, the serious problem of wind erosion in open-pit mining areas has been solved, and good wind erosion resistance and weather resistance are achieved, economical and environmentally friendly, which is in line with the concept of green development.
Patent Information
- Application Number
- CN202510294829.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-15
AI Technical Summary
The soil in open-pit mining areas has severe wind erosion, and traditional wind erosion resistance technology is costly and has limited effect. It requires a new type of sand fixing agent that is environmentally friendly, cheap, efficient and multifunctional.
A crusting material with crosslinking network structure is developed, using polyvinyl alcohol, sodium alginate and glycerol as functional main materials, sodium trimetaphosphate and calcium chloride as crosslinking agents, and sodium dodecylbenzenesulfonate as surfactant. Its performance is verified through indoor wind corrosion experiments, freeze-thaw cycle experiments, dry-wet alternating experiments, and salt resistance tests.
It has achieved good wind corrosion resistance and weather resistance, economy and environmental protection, and its degradability conforms to the concept of green development, which can effectively reduce soil wind corrosion losses and improve the safety of the ecological environment of the mining area.
Smart Images

Figure CN119823722A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal ion treatment in solidified coal gangue, and in particular to a crusting material with a cross-linked network structure and a preparation method and application thereof. Background Art
[0002] In the process of open-pit mining, the overburden on the coal seam needs to be completely stripped off, which destroys the original stratigraphic sequence and structure, interferes with the growth and reproduction of microorganisms in the soil, weakens the fertility of the soil, and damages the ecological environment of the vegetation in the mining area. The mining area in a certain region is located in an ecologically fragile area with severe land desertification and soil erosion. It belongs to the continental arid desert climate, and the annual temperature difference and diurnal temperature difference in the area are also prominent. The dry air, high evaporation, and perennial windy and scarce precipitation provide conditions for the development of wind erosion. On the one hand, wind erosion causes soil degradation and fertility decline by directly consuming fine particles and related nutrients, accelerating the degradation of the mining area ecosystem. On the other hand, wind erosion causes serious air pollution, which not only seriously threatens the physical and mental health of workers in the mining area, but also reduces visibility on the open-pit mine platform and roads, thereby threatening driving safety and reducing production and transportation capacity. It can be seen that the environmental problems caused by wind erosion in open-pit mining areas need to be solved urgently.
[0003] In order to prevent and control the hazards of wind erosion in open-pit mining areas, many anti-wind erosion technologies and measures have been developed. Traditional measures include watering the mining area, covering with tarpaulins, and windbreaks, but they are costly and have limited anti-wind erosion capabilities. Compared with traditional measures, the application of crusting materials has the advantages of saving water resources and having good anti-wind erosion effects, and therefore has received widespread attention. The chemical crust formed by spraying crusting materials can solve the problem of wind-blown dust in an efficient and environmentally friendly way. At present, crusting materials can be divided into traditional and new sand-fixing agents. According to the differences in mechanism, traditional sand-fixing agents are divided into three types: wetting type, condensation type, and condensation type.
[0004] Traditional sand-fixing agents have a certain anti-wind erosion effect, but they still have disadvantages such as low sand-fixing efficiency, serious pollution, high corrosion, high cost, and chemical hazard risks, which need to be further improved. Therefore, researchers began to study new sand-fixing agents with the goal of being environmentally friendly, cheap, efficient, and multifunctional. Summary of the invention
[0005] In view of the limitations of the above-mentioned prior art, the present invention provides a crusting material with a cross-linked network structure, and a preparation method and application thereof. In view of the soil wind erosion problem in the open-pit mine dump, the present invention develops a crusting material with polyvinyl alcohol, sodium alginate and glycerol as functional main ingredients, sodium trimetaphosphate and calcium chloride as cross-linking agents, and sodium dodecylbenzene sulfonate as a surfactant. Using viscosity, hardness, permeability and anti-evaporation performance as experimental indicators, the optimal ratio of the crusting material was explored, and it was proved through indoor wind erosion experiments, freeze-thaw cycle experiments, dry-wet alternation experiments, and salt resistance that the crusting material has good wind erosion resistance and weather resistance, economy and environmental protection.
[0006] To achieve the above object, the present invention adopts the following technical solution: The first aspect of the present invention is to provide a skinning material with a cross-linked network structure, wherein the material is a skinning material with a double network cross-linked structure obtained by reacting raw materials including a functional main ingredient, a cross-linking agent, and a surfactant; the functional main ingredient includes a water-soluble high molecular polymer, alginate, and a polyol; The cross-linking agent includes cross-linking agent 1 and cross-linking agent 2; the cross-linking agent 1 is trimetaphosphate; the cross-linking agent 2 is a soluble calcium salt; and the cross-linking agent is chloride.
[0007] As a preferred embodiment, the water-soluble high molecular polymer is polyvinyl alcohol; The alginate is sodium alginate; The polyol is glycerol; The surfactant is alkylbenzene sulfonate.
[0008] As a preferred embodiment, the water-soluble high molecular polymer is 1799 type polyvinyl alcohol; The first cross-linking agent is sodium trimetaphosphate; The second cross-linking agent is calcium chloride; The surfactant is sodium dodecylbenzene sulfonate.
[0009] As a preferred embodiment, the following raw materials are included in parts by weight: Sodium alginate: 0.4-0.8 parts; Polyvinyl alcohol is 3 to 8 parts; Glycerin is 3 to 7 parts; Sodium trimetaphosphate is 0.04 to 0.20 parts; Calcium chloride is 0.02-0.1 parts; Sodium dodecylbenzene sulfonate is 0.5-0.8 parts.
[0010] As a preferred embodiment, the following raw materials are included in parts by weight: Sodium alginate: 0.4-0.6 parts; Polyvinyl alcohol is 4 to 6 parts; Glycerin is 4 to 6 parts; Sodium trimetaphosphate is 0.08 to 0.16 parts; Calcium chloride is 0.04-0.06 parts; Sodium dodecylbenzenesulfonate is 0.55-0.65 parts.
[0011] The second aspect of the present invention is to provide a method for preparing the skinning material with a cross-linked network structure according to the first aspect of the present invention, comprising the following steps: (1) Under heating conditions, adding a water-soluble polymer to water and mixing the mixture evenly to obtain a water-soluble polymer solution; (2) Under heating conditions, adding alginate to a solution of a water-soluble high molecular polymer and mixing evenly, adding polyol and mixing evenly, to obtain a mixed solution of functional main ingredients; (3) adding alkaline solution to adjust the pH of the mixed solution of the functional main ingredients, continuing to stir for a period of time, first adding the crosslinking agent 1 and mixing evenly, adding water, and then adding the solution of the crosslinking agent 2 and mixing evenly; finally adding the surfactant and mixing evenly to obtain the skinning material with the crosslinked network structure.
[0012] As a preferred embodiment, step (1): The heating temperature is 90-95°C; Step (2), The heating temperature is 40-55°C; Step (2), the alginate is added to the water-soluble polymer solution and the mixing time is 2.5-3.5 hours; The time for adding polyol and mixing evenly is 0.5-1.5 h.
[0013] As a preferred embodiment, step (3), The lye is a solution of sodium hydroxide; Adjusting the pH of the mixed solution of the functional main ingredients to 9.5-10.5; Continue stirring for 25-35 min.
[0014] As a preferred embodiment, step (3), The alkali solution is a sodium hydroxide solution with a concentration of 0.9-1.2 mol / L; The time for adding the crosslinking agent and mixing evenly is 2.5-3.5 h; Add water to make the volume of the solution 230-260ml; The volume of the solution containing the cross-linking agent 2 is 23-26 ml.
[0015] The third aspect of the present invention is to provide a use of a crusting material having a cross-linked network structure as described in the first aspect of the present invention in dust control.
[0016] The present invention has the following advantages: The present invention aims at the serious problem of wind erosion of soil in open-pit mine dumps, and develops a crusting material with polyvinyl alcohol, sodium alginate and glycerol as functional main ingredients, sodium trimetaphosphate and calcium chloride as cross-linking agents, and sodium dodecylbenzene sulfonate as a surfactant. The crusting material of the present invention is degradable and conforms to the concept of green development. The crusting material of the present invention has good wind erosion resistance and has certain weather resistance to cold, heat, water and sodium salt. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The infrared spectra of sodium alginate, polyvinyl alcohol and crusting materials are shown; Figure 2 The SEM and EDS images of the skin material film of the present invention; Figure 3 It is a schematic diagram of the reaction system of the present invention; Among them, (a) is the ionic cross-linked structure formed by SA and calcium chloride; (b) is the cross-linked network formed by PVA, SA and STMP; (c) is the hydrogen bond formed in the system; Figure 4 is the degradation rate of the cured film of the crusting material of the present invention over time; Figure 5 The crusting conditions formed by the crusting material of the present invention at different application amounts; Figure 6 The soil erosion rate under different dosages of the crusting material of the present invention; Figure 7 Hardness changes of specimens of crusting materials and soil stabilizers applied for freeze-thaw cycles; Figure 8 Hardness changes of specimens of crusting materials and soil stabilizers applied for alternating wet-dry processes; Fig. 9 Changes in hardness of crusting materials and soil stabilizer specimens applied for sodium chloride and sodium sulfate salt treatments. DETAILED DESCRIPTION
[0018] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0019] abbreviation: SEM: scanning electron microscope; EDS: Energy Dispersive Spectrometer; PVA: polyvinyl alcohol; SA: sodium alginate; STMP: Sodium trimetaphosphate; Gly: Glycerol; SDBS: sodium dodecyl benzene sulfonate.
[0020] Test method: Viscosity test Viscosity is one of the important performance indicators of soil crust materials, which is used to measure the bonding effect of crust materials on soil particles. This test is based on the rotation method in GB / T10247-2008 to measure the viscosity of the sample, and the equipment used is a rotational viscometer (RheolabQC).
[0021] Hardness test The hardness of the material is used to reflect the compressive strength of the sample after it is applied on the topsoil to form a crust, and is one of the important indicators for testing the performance of the crust material. The LX-A Shore hardness tester is used to test the hardness of the sample.
[0022] Water retention test The water retention rate is used to evaluate the water retention performance of the crusting material. The higher the water retention rate, the stronger the water retention capacity. The test steps are as follows: (1) Prepare 18 600g soil fugitive dust samples and dry them at 75℃ in a forced air drying oven (temperature control range: 10-300℃).
[0023] (2) Place the treated soil sample (600 ± 0.05 g) into a culture dish with an inner diameter of 12.5 ± 0.1 cm and a height of 63 mm.
[0024] (3) Spray the prepared mixed solutions of different concentrations evenly on the surface of the soil dust sample. After 48 hours of complete solidification, record the weight of the sample. The water retention rate is calculated according to the following formula.
[0025] (3.1) In the formula, MRR (%) is the water retention rate, m1 (g) is the weight of the culture dish after spraying the crusting material; m2 (g) is the weight of the culture dish measured after 48 h; m3(g) is the weight of the sprayed crusting material.
[0026] Penetration Testing The experiment was conducted in accordance with the penetration rate method in GB / T16913-2008 “Test method for physical properties of dust”, and the wetting rate was used to reflect the wettability of the material to the soil.
[0027] Degradation rate test In order to evaluate the biodegradability of the crusting material, a degradation rate test was conducted. The steps are as follows: (1) Spray the crusting material onto a glass plate (thickness less than 2 mm), place the glass plate in a vacuum drying chamber, and dry it at 60°C until the weight is constant.
[0028] (2) The completely dried crust material was placed on the top layer of the soil in a 500 mL jar, and the jar was then placed at room temperature (25°C) for 14 cycles (1 cycle was 5 days).
[0029] (3) Take out the cured film in the tank and dry it. The degradation rate is calculated as follows: (3.2) in: is the initial mass of the crusting material, mg; is the mass of crusting material after a certain period of time, mg; μ is the degradation rate of the crusting material.
[0030] During the degradation process, SA is first invaded by microorganisms (such as fungi and bacteria) in the soil, and PVA and Gly can react with metal salts in the soil to form peroxides. Peroxides can break molecular chains and lead to lower molecular weights, further forming low molecular weight polymers. The polymers are degraded into carbon monoxide and water, indicating that the crusting material is biodegradable in the soil, in line with the concept of green development, and will not cause secondary pollution.
[0031] Example 1 A method for preparing a skinning material with a cross-linked network structure comprises the following steps: (1) Preparation of PVA solution: Place a 500 ml conical flask in a water bath, slowly and evenly add polyvinyl alcohol (PVA) and 150 ml of water, adjust the temperature to 95 °C and stir magnetically for 3 h to prepare a PVA aqueous solution.
[0032] (2) Synthesis of the main material: Adjust the temperature of the water bath to 50°C. When the temperature stabilizes at 50°C, slowly add sodium alginate (SA) powder to the PVA solution in batches and stir magnetically for 3 h. Then add glycerol (Gly) and stir magnetically for 1 h until it dissolves.
[0033] (3) Cross-linking of polymer chains: The pH of the solution was adjusted to 10 by adding 1.0 M NaOH. After 30 minutes, sodium trimetaphosphate (STMP) was added to the solution and magnetically stirred for 3 hours until it was completely dissolved. Under alkaline conditions, the phosphate groups of STMP reacted with the hydroxyl groups of PVA and SA to form new bonds by chemical cross-linking. Water was added to 250 ml. Then calcium chloride solution was added and magnetically stirred until dissolved. Finally, sodium dodecylbenzene sulfonate was added and magnetically stirred until dissolved.
[0034] The added amounts of sodium alginate, polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate in the above embodiment are shown in Table 1.
[0035] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0036] Example 2 The same preparation method is used as in Example 1, except that the added amounts of polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate are different. The specific added amounts of each raw material are shown in Table 1.
[0037] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0038] Example 3 The same preparation method is used as in Example 1, except that the added amounts of polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate are different. The specific added amounts of each raw material are shown in Table 1.
[0039] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0040] Example 4 The same preparation method is used as in Example 1, except that the added amounts of polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate are different. The specific added amounts of each raw material are shown in Table 1.
[0041] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0042] Example 5 The same preparation method is used as in Example 1, except that the added amounts of polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate are different. The specific added amounts of each raw material are shown in Table 1.
[0043] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0044] Example 6 The same preparation method is used as in Example 1, except that the added amounts of polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate are different. The specific added amounts of each raw material are shown in Table 1.
[0045] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0046] Example 7 The same preparation method is used as in Example 1, except that the added amounts of polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate are different. The specific added amounts of each raw material are shown in Table 1.
[0047] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0048] The crusting material prepared in Example 7 was subjected to infrared testing and the qualitative and semi-quantitative results of EDS elemental analysis of the film after the crusting material was dried were as follows: Figure 1 and Figure 2 As shown, Figure 1 (a), (b) and (c) show the infrared spectra of SA, PVA and crusting material films respectively. From the infrared spectrum of SA, it can be seen that the peak at 3438 cm -1 It is attributed to the stretching vibration of -OH, with a peak at 1026 cm -1 The peak at 1617 cm is attributed to the stretching vibration of the CO bond connecting the hydroxyl group. -1 It is attributed to the antisymmetric stretching vibration peak of the CO bond in the carboxylate. From the PVA spectrum, it can be seen that the peak is at 847 cm -1 It is attributed to the CC stretching vibration, with a peak at 1097 cm -1 It is attributed to the stretching vibration of CO, with a peak at 1441 cm -1 The peak at 3422 cm is attributed to the bending vibration of -CH -1 It is attributed to the stretching vibration of -OH.
[0049] In the prepared crust material, the characteristic absorption peaks of SA and PVA both appeared, and the stretching vibration absorption peak of -OH red-shifted to 3264 cm -1 , indicating that hydrogen bonds are generated between the components in the mixture (the hydrogen bonds are mainly generated by PVA and GLY, PVA and SA, and SA and GLY). The absorption peak appears at 1037 cm -1 It is the stretching vibration peak of the POC bond, indicating that cross-linking occurs between PVA-SA-GLY (hydrogen bond) and SA-STMP (skeleton), forming a double cross-linked network structure in the system.
[0050] Figure 2 The qualitative and semi-quantitative results of EDS elemental analysis of the film after the crusting material is dried are shown. From the element distribution diagram, it can be seen that the material contains C, O, Na, P, and Ca elements and is evenly distributed. Among them, the peaks of C and O are relatively strong, accounting for 57.43wt% and 39.64wt% respectively, that is, the main part of the material is composed of C and O. The synthesized material contains 0.28wt% Ca. Preliminary analysis shows that the introduction of Ca is due to the participation of calcium chloride in the ionic cross-linking reaction. The presence of Ca indicates that calcium ions successfully promote the cross-linking reaction of SA.
[0051] The reaction diagram of the whole system of the crust material prepared by the present invention is as follows: Figure 3 As shown. In the reaction system, sodium alginate and polyvinyl alcohol are the substrates of the reaction, providing cross-linking sites for the subsequent polymerization of glycerol, sodium trimetaphosphate and calcium chloride. Sodium trimetaphosphate acts as a cross-linking agent to complete the chemical cross-linking between polymers, and then forms a network structure through calcium ions and sodium alginate ions. Sodium dodecyl sulfate is an emulsifier that can effectively improve the solubility and wetting properties of the material. Sodium alginate and polyvinyl alcohol are monomers that form a network matrix, which makes the material sticky and adsorbable, and enhances its stability and mechanical properties; specifically, according to the preparation steps, sodium alginate, polyvinyl alcohol, glycerol, sodium trimetaphosphate and calcium chloride react through the following steps. (1) Polyvinyl alcohol is completely dissolved in water to form a polyvinyl alcohol aqueous solution, and the polyvinyl alcohol molecular chains are physically cross-linked through interchain hydroxyl hydrogen bonds to form cross-linking points. After sodium alginate is dissolved in the polyvinyl alcohol aqueous solution, the physical cross-linking between the hydroxyl groups of polyvinyl alcohol and the hydroxyl groups of sodium alginate will form intermolecular hydrogen bonds, thereby initially forming a three-dimensional physical cross-linked network structure (such as Figure 3 c) H-bonds Ⅰ, Ⅱ, Ⅲ). (2) Glycerol itself contains a large number of hydroxyl groups, which will form strong intramolecular and intermolecular hydrogen bonds with the hydroxyl groups of sodium alginate and polyvinyl alcohol (such as Figure 3c shows the hydrogen bonding between polyvinyl alcohol and glycerol), increasing the intermolecular forces, which is conducive to the aggregation of molecular chains, has a certain adhesion, and increases the viscosity of the material. Due to the strong hydrogen bonding, a SA-PVA-Gly three-dimensional physical cross-linked network structure is formed. (3) Under alkaline conditions, the added sodium trimetaphosphate can react chemically with the hydroxyl groups in the sodium alginate and polyvinyl alcohol polymers (such as Figure 3 b) Promote the formation of a network structure between high molecular weight polymers. This chemically cross-linked network structure has a strong cohesive force. It can effectively bind dust particles. (4) When a water-soluble calcium salt is introduced into a high molecular weight polymer solution, the calcium ions in the calcium chloride can form a coordination effect with the G fragment in the sodium alginate molecular chain and the carboxyl group (-COO-) of the adjacent G fragment, thereby physically cross-linking the linear molecular chain of sodium alginate to form a SA network through an "egg-box" structure (such as Figure 3 a).
[0052] Example 8 The same preparation method is used as in Example 1, except that the added amounts of polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate are different. The specific added amounts of each raw material are shown in Table 1.
[0053] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0054] Example 9 The same preparation method is used as in Example 1, except that the added amounts of polyvinyl alcohol, glycerol, sodium trimetaphosphate, calcium chloride and sodium dodecylbenzene sulfonate are different. The specific added amounts of each raw material are shown in Table 1.
[0055] The properties of the skin material with a cross-linked network structure prepared by the above method are shown in Table 1.
[0056] Table 1
[0057] When the viscosity is 70-85cP, it not only ensures the adhesion of the crusting material to the soil particles, but also avoids the problem of clogging during the spraying construction process. The precipitation in the mining area is relatively small, so the anti-evaporation performance of the crusting material should be improved as much as possible to achieve the maximum water retention effect. The hardness can reflect the mechanical properties and anti-interference ability of the soil solidification layer, and the hardness of the solidification layer should be increased as much as possible. When selecting the penetration rate, it is advisable to select 0.4-0.6mm / min. Too slow a penetration rate will affect the effective wetting depth of the crusting material, thereby affecting the application effect; and too fast a penetration rate will affect the hardness of the film, resulting in the inability to form a complete and stable solidification layer, thereby reducing the consolidation ability of the material. The performance of the crusting material prepared in the above embodiments of the present invention meets the above requirements and has excellent comprehensive performance.
[0058] The degradation results of the crust material prepared in Example 9 are tested as follows: Figure 4 shown.
[0059] Figure 4 The degradation rate of the crusting material film over time is shown. As can be seen from the figure, the degradation rate of the film gradually increases with time. After 10 days of degradation, the crusting material film showed a significant decrease in mass, and the degradation rate was significantly accelerated. This mass decay is likely caused by the combined action of air, water and microorganisms in the soil. After 12 cycles, the degradation rate of the film reached 10.87%, indicating that its effective degradation period is relatively long. After 60 days, the quality of each film was relatively stable, and the mass residual rate was maintained at about 89%, indicating that the material was in a relatively stable state at this stage. During the degradation process, SA was first invaded by microorganisms (such as fungi and bacteria) in the soil, and PVA and Gly could react with metal salts in the soil to form peroxides. Peroxides can destroy molecular chains and lead to lower molecular weights, further forming low molecular weight polymers. The polymers are degraded into carbon monoxide and water, indicating that the crusting material is biodegradable in the soil, which is in line with the concept of green development and will not cause secondary pollution. It can be seen that the prepared crusting material not only has good degradation performance and conforms to the concept of environmental protection, but also can maintain the relative stability of material properties for a long time.
[0060] Example 10 The crust material prepared in Example 9 was heated at 1 kg / m 2 , 1.5kg / m 2 , 2kg / m 2 , 2.5kg / m 2 , 3kg / m 2 3.5kg / m 2 Six different application rates were sprayed on the soil surface to observe the integrity of the dust surface crust and its wind erosion resistance. Figure 5 and Figure 6 shown.
[0061] Test method: Wind erosion experiment In order to verify the actual application effect of the crusting material, an anti-wind erosion test was designed to simulate the natural wind in an open-pit coal mine. This experiment uses an axial flow fan to generate wind, and the first measuring point No. 1 is located 0.3m away from the fan outlet. After this position, a measuring point is set every 0.5m, for a total of 3 measuring points. The wind speed at each point is collected by an anemometer, and the average of three repetitions is taken as the final value. For each test, a soil sample to be tested is placed at each measuring point, and soil stabilizer or crusting compound solution is sprayed on the sample. After the sprayed solution is naturally dried, the fan is started.
[0062] Before exposing the specimens to the induced wind, measure the mass of each specimen and record it as Then place the specimen at the measuring point and adjust the fan frequency through the speed motor controller to control the induced wind speed. After running the fan, measure the total mass of the specimen every 1 hour and record it as f Repeat this process. After the test, determine the soil loss rate of each sample. (kg / m 2 ), defined as per unit surface area (m 2 ) The mass of soil eroded by wind (g) is calculated as follows: (4.1) Where A is the surface area of the soil sample after treatment, m 2 .
[0063] Figure 5 1kg / m 2 , 1.5kg / m 2 , 2kg / m 2 , 2.5kg / m 2 , 3kg / m 2 3.5kg / m 2 Photos of soil treatment before and after wind erosion test at 12 m / s wind speed at 6 application rates, and the crust formation. 2 and 1.5kg / m 2 The samples treated with crusting materials showed obvious signs of wind erosion. The fine dry aggregate was first consumed by wind erosion, and the particle size became coarser at the cracked part of the solidified layer. When the amount of crusting material sprayed was small, the amount of material penetration on the soil surface was small, and the surface soil could not be completely wetted or the wetting depth was insufficient, resulting in a thin film, making the surface of the solidified layer easy to crack and reducing the anti-wind erosion efficiency. 2 , 2.5kg / m 2 , 3kg / m 2 3.5kg / m 2 At the application rate, the crust thickness was 18.23mm, 20.23mm, 21.96mm, and 25.98mm respectively, and the crust thickness increased with the increase of application rate. When the spraying concentration is increased, the film-forming effect on the soil surface is good, so the surface will not be cracked or damaged, and the solidified layer formed is thicker. 2 , 3kg / m 2 3.5kg / m 2 There was little evidence of wind erosion at the applied rate, indicating that the formed cured layer maintained good integrity and hardness.
[0064] Figure 6is the anti-wind erosion efficiency of soil dust samples at different spraying rates at a wind speed of 12 m / s. Figure 5 The test results show that under different spraying rates, the soil loss rate generally increases with the extension of wind erosion time, and the erosion rate gradually slows down. 2 In the first 30 minutes of erosion under the spraying amount, the soil loss rate was as high as 31.21g / m 2 This is because the amount of spraying is too small to form a complete soil crust. The fine-grained soil particles exposed on the surface are highly erodible and are blown away first. After 2 hours of blowing, the soil erosion rate dropped significantly. With the increase of the amount of spraying, the soil loss rate showed a downward trend. The spraying amount was 1kg / m 2 and 2.5kg / m 2 After 3 hours of blowing, the soil erosion rates of the samples were 57.64 g / m 2 and 38.64g / m 2 , a decrease of 32.96%. The spraying amount is 3.5kg / m 2 After 3 hours of blowing, the soil erosion rate of the sample reached 37.69g / m 2 , and the spraying rate is 2.5kg / m 2 Compared with the samples of 2 , a decrease of 2.46%. In summary, the spraying rate is 2.5kg / m 2 The sample has the most cost-effective wind erosion resistance.
[0065] In summary, it can be seen that when the crusting material is 2.5kg / m 2 The cured layer formed under the application rate maintains good integrity and hardness. The application rate is 2.5kg / m 2 At a wind speed of 12 m / s, after 3 hours of blowing, the soil erosion rate was 38.64 g / m 2 , while the soil erosion rate of the untreated soil was greater than 1500g / m after 3h of blowing. 2It can be seen that the crusting material of the present invention greatly reduces the amount of soil mass loss, because after spraying the crusting material, the penetration, wetting and bonding between soil particles are guaranteed, and the anti-wind erosion performance is good. The surfactant sodium dodecylbenzene sulfonate contained in the crusting material increases the surface wettability of soil particles, making the crusting material easy to penetrate into the gaps between soil particles, filling the gaps between particles, and enhancing the agglomeration effect. The three-dimensional network cross-linked structure formed by cross-linking STMP, SA and PVA has bonding properties. The PVA-Gly-SA component in PVA-Gly-SA-STMP / SDBS contains abundant hydroxyl groups, which can electrostatically interact with the N-containing functional groups in the soil sample particles and hydrogen bond with the oxygen-containing functional groups in the soil sample. Therefore, PVA-Gly-SA-STMP / SDBS can make the surface soil sample bond and solidify, and enhance the agglomeration of particles. With the absorption of heat in the outside air, the water attached to the soil surface gradually evaporates, thereby continuously reducing the water content. SA is rich in hydroxyl and carboxyl groups. As a solvent, it will quickly lose free water, but it can keep the moisture of the solidified layer, prevent the solidified layer from cracking after drying, and reduce the evaporation rate of water. Gly has hygroscopic and water-retaining properties, can effectively fix fine soil particles, and produce strong agglomeration and precipitation effects. Therefore, the crusting material of the present invention has good wettability, moisture retention and wind erosion resistance.
[0066] Embodiment 11 The crust material prepared in Example 9 (hereinafter referred to as J) was heated at 2.5 kg / m 2 Spray the application amount on the soil surface.
[0067] Comparative Example 1 It adopts the same treatment method and testing method as Example 11, the difference is that the existing soil stabilizer is used. The soil stabilizer is produced by Langfang Peter Sealing Materials Co., Ltd., which is an environmentally friendly crusting type soil stabilizer. The main components are cellulose and xanthan gum. It is a multifunctional high molecular polymer (hereinafter referred to as W), has no obvious irritating odor, is milky white, and has a neutral pH.
[0068] The samples prepared in the above-mentioned Example 11 and Comparative Example 1 were subjected to freeze-thaw cycle test, dry-wet alternation test and salt resistance test to evaluate the weather resistance and wind erosion resistance of the crusting materials.
[0069] Test method: Dry-wet alternation experiment The surface treated samples were subjected to a dry-wet cycle. The main steps are as follows: (1) Spray the crusting material into the dust sample and then cure it for 48 hours to ensure that the solution is completely dry.
[0070] (2) Spray each sample with the same amount of water as the surface treatment every 24 hours for 6 days.
[0071] (3) At the end of the 8-day cycle, the samples were subjected to wind erosion testing to study the weathering resistance of the soil stabilizer treated samples during 6 dry-wet cycles. Another 8-day dry-wet cycle was performed to test the effect of the dry-wet cycle on the hardness of the stabilizer.
[0072] Freeze-thaw cycle experiment The low temperature weather resistance of the two materials can be examined from two aspects: wind erosion and hardness change. The experimental steps are as follows: (1) Prepare two samples to be tested and spray them on the surface of the dust sample. Allow them to cure for 48 hours to ensure that the solution is completely dry. Set up five parallel samples for each sample to confirm the repeatability of the results.
[0073] (2) At the beginning of each freeze-thaw cycle, place the two treated specimens in a freezer at a constant temperature of -20°C and freeze for 24 h.
[0074] (3) Place the sample in an oven at 50 degrees Celsius for 24 hours. Repeat the above steps until the number of freeze-thaw cycles reaches 5 times.
[0075] (4) After the five cycles, the samples were subjected to wind erosion tests to study the weather resistance of the samples after five freeze-thaw cycles.
[0076] The higher the hardness of the consolidation layer, the stronger the material's ability to resist natural erosion and human damage. After each freeze-thaw cycle, the crust material and stabilizer-impregnated samples were taken out of the 50°C oven and cooled to room temperature for hardness testing.
[0077] Salt tolerance test In order to test the salt resistance of the crusting material, sodium chloride and sodium sulfate were prepared into a mixed salt-alkali at a molar ratio of 1: 1. To simulate different degrees of water salinity, different salt content solutions were prepared according to the application amount of 5g / kg, 10g / kg, 20g / kg, 40g / kg, and 60g / kg, respectively, and applied to the soil (i.e., soil with a salt content of 0.5%, 1%, 2%, 4%, and 6%), and the application amount of the crusting material according to Example 11 and Comparative Example 1 was tested in conventional soil stabilizers and newly developed crusting materials to obtain the marked final product. The consistency of the bulk density of each sample is ensured during the preparation process to reduce the variability of the crusting sample itself. After the salt-containing samples treated with two different materials are completely cured at room temperature, the samples are subjected to wind erosion tests to explore the soil-fixing ability of the two materials corresponding to soils of different salinities.
[0078] The soil loss rates of the products of Comparative Example 1 and Example 11 were tested at a wind speed of 12 m / s. After 8 hours of wind erosion, the soil loss rates of Example 11 and Comparative Example 1 were 9.87 g / m 2 , 11.46g / m 2 Compared with the CG (untreated original soil sample) treated with wind erosion for 8 hours, the soil loss rate of Example 11 and Comparative Example 1 decreased by 99.48% and 99.40%, respectively. It can be seen that the anti-wind erosion effect of Example 11 and Comparative Example 1 is outstanding, and the anti-wind erosion effect of Example 11 is better.
[0079] The soil loss of the soil samples prepared by the crusting material (J) and the soil stabilizer sample (W) before and after 5 freeze-thaw cycles in a strong wind of 12 m / s was tested. The soil loss rate of the surface-applied crusting material and soil stabilizer after 5 freeze-thaw cycles gradually increased with the increase of the cumulative duration of wind erosion. After 12 hours of wind erosion at 12 m / s, the soil loss rates were 31.53 g / m 2 , 42.36g / m 2 ,Compared with the soil loss rate of the original soil sample under wind erosion, the two materials have good anti-wind erosion effect after freeze-thaw cycles, indicating that both materials have anti-freeze properties.
[0080] Figure 7 The hardness changes of the crust material (J) and soil stabilizer samples (W) applied during the freeze-thaw cycle process show that the hardness of the surface shell of the sample first increased and then decreased after the application of the two materials. After 5 freeze-thaw cycles, the hardness of the crust material decreased from 68.69HA to 65.25HA, a decrease of only 5%. The hardness of the soil stabilizer decreased from 60.63HA to 56.25HA, a decrease of 7.22%, indicating that the compressive consolidation characteristics of the two materials are relatively stable, and the strength decay process is relatively slow under drastic temperature changes. In particular, the hardness loss of the crust material is less, which is due to the large number of hydrogen bonds formed between glycerol, sodium alginate and polyvinyl alcohol in the material and the ionic crosslinking between calcium ions and sodium alginate, which improve the antifreeze performance of the material.
[0081] Figure 8The changes in the hardness of the crusting material and the soil stabilizer crust after five wet-dry cycles are shown. After the first wet-dry cycle, the hardness of the solidified layer of the sample with soil stabilizer applied on the surface increased by 6%, and no cracking was found in the surface solidified layer. This is because some soil stabilizers remain on the surface of the sample in the initial stage after spraying and fail to penetrate between the particles and play a bonding role. During the first wet treatment, a fixed amount of water was sprayed vertically on the sample, so that the soil stabilizer remaining on the surface of the sample was further penetrated into the particles with water. After the sample was dried, a consolidation crust was formed on the surface again, fully demonstrating the "bridging and supporting" role of the soil stabilizer, thereby increasing the hardness of the sample. The reduction in hardness during the second wet-dry cycle was caused by the downward penetration and loss of xanthan gum in the soil stabilizer after dissolving in water. After two wet-dry cycles, the hardness of the solidified layer fluctuated and tended to decrease overall. After the fifth wet-dry cycle, the hardness decreased by 19.2%. This is because the microstructure formed between the biopolymer and the surface of the sand particles was destroyed during the wetting process.
[0082] The hardness of the sample with crusting material applied on the surface first decreased and then fluctuated after five dry-wet cycles. After two dry-wet cycles, the hardness of the solidified layer decreased by 10%. This is because during the dry-wet cycle, the humidification process increases the relative humidity in the air, moisture enters the soil, and the effective components of the crusting material in the solidified layer dissolve in water and then infiltrate. The dehumidification process removes moisture from the soil. The interaction between moisture and the soil of the crusting material causes the shrinkage and swelling cycle of the solidified layer and the loss of effective components, resulting in damage to the surface solidified layer, causing its hardness to show a downward trend and variability. After two dry-wet cycles, the hardness of the solidified layer formed by the crusting material also fluctuates and shows an overall downward trend. After the fifth dry-wet cycle, the hardness decreased by 16.7%, still maintaining the original 83.3%. This is because during the wetting process, sodium alginate, as a fast-absorbing swelling glue, can absorb 200 to 300 times its own weight of water, thereby improving the water tolerance of the crusting material.
[0083] Fig. 9The hardness changes of the samples treated with crusting materials and soil stabilizers for sodium chloride and sodium sulfate salts show that after the application of the two materials, the hardness of the surface shell of the samples shows an increasing trend with the increase of soil salt content. The salt content of the samples with crusting materials applied on the surface increased from 0.5% to 6%, and the hardness of the solidified layer increased significantly from 61.6HA to 82HA, an increase of 33.1%. This is because when the original treated samples are in a dry state, there is air in the macropores and mesopores between the particles, and the liquid material tends to flow to the micropores. Applying sodium sulfate and sodium chloride solutions fills and stabilizes the pores in the soil, allowing the sodium salt to act as part of the soil skeleton. This pore filling significantly improves the strength of saline-alkali soil. The "egg box" structure produced by the cross-linking of calcium chloride and sodium alginate ions in the crusting material is relatively stable and can withstand the influence of saline-alkali environments. Some substances present in saline soils include Na + , Cl - 、CO3 2- , SiO2. The interaction of these substances and the bonding properties of the crusting materials enhance the cohesion of soil particles and the stability of the structure, and greatly improve the soil strength. The salt content of the sample with soil stabilizer applied on the surface increased from 0.5% to 6%, and the hardness of the solidified layer increased from 60HA to 68.3HA, an increase of 13.8%. The improvement of the hardness of solidified saline soil is mainly due to the bonding effect of xanthan gum and cellulose on the basis of improving the hardness of saline-alkali soil. These gelling substances are intertwined and accumulated in space, which enhances the cementation between soil particles.
[0084] In addition, the annual total costs of spraying the crusting material of the present invention, the soil stabilizer of the commercially available material, and water are 2.381 million yuan, 2.978 million yuan, and 2.441 million yuan, respectively. The direct cost of spraying the crusting material of the present invention is better than sprinkling water and spraying commercially available materials. The annual cost of the crusting material of the present invention is 3.37% lower than that of water, and the cumulative effective time of the crusting material of the present invention is 45 times that of water; the direct cost of spraying the crusting material of the present invention is 25.1% lower than that of similar commercially available materials. Analyzing the economic benefits and social benefits, the application effect of the crusting material of the present invention is remarkable.
[0085] In summary, the present invention aims at the soil wind erosion problem of open-pit mine dumps, and develops a crusting material with polyvinyl alcohol, sodium alginate and glycerol as functional main ingredients, sodium trimetaphosphate and calcium chloride as cross-linking agents, and sodium dodecylbenzene sulfonate as a surfactant. Viscosity, hardness, permeability and anti-evaporation performance are used as experimental indicators to explore the optimal ratio of the crusting material and prove that the crusting material has good wind erosion resistance and weather resistance, economy and environmental protection through indoor wind erosion experiments, freeze-thaw cycle experiments, dry-wet alternation experiments, and salt resistance.
[0086] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A skinning material with a cross-linked network structure, characterized in that: The material is a crusting material with a double network cross-linking structure obtained by reacting raw materials including a functional main ingredient, a cross-linking agent, and a surfactant; the functional main ingredient is a water-soluble high molecular polymer, alginate, and a polyol; The water-soluble high molecular polymer is polyvinyl alcohol; the polyol is glycerol; the surfactant is alkylbenzene sulfonate; The cross-linking agents are cross-linking agent 1 and cross-linking agent 2; the cross-linking agent 1 is trimetaphosphate; the cross-linking agent 2 is a soluble calcium salt; and the cross-linking agent 2 is a chloride salt.
2. The skinning material with a cross-linked network structure according to claim 1, characterized in that: The alginate is sodium alginate; The water-soluble high molecular polymer is 1799 type polyvinyl alcohol; The first cross-linking agent is sodium trimetaphosphate; The second cross-linking agent is calcium chloride; The surfactant is sodium dodecylbenzene sulfonate.
3. The skinning material with a cross-linked network structure according to claim 2, characterized in that: The invention comprises the following raw materials in parts by weight: Sodium alginate: 0.4-0.8 parts; Polyvinyl alcohol is 3 to 8 parts; Glycerin is 3 to 7 parts; Sodium trimetaphosphate is 0.04 to 0.20 parts; Calcium chloride is 0.02-0.1 parts; Sodium dodecylbenzene sulfonate is 0.5-0.8 parts.
4. The skinning material with a cross-linked network structure according to claim 3, characterized in that: The invention comprises the following raw materials in parts by weight: Sodium alginate: 0.4-0.6 parts; Polyvinyl alcohol is 4 to 6 parts; Glycerin is 4 to 6 parts; Sodium trimetaphosphate is 0.08 to 0.16 parts; Calcium chloride is 0.04-0.06 parts; Sodium dodecylbenzenesulfonate is 0.55-0.65 parts.
5. The method for preparing a skinning material with a cross-linked network structure according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Under heating conditions, adding a water-soluble polymer to water and mixing the mixture evenly to obtain a water-soluble polymer solution; (2) Under heating conditions, adding alginate to a solution of a water-soluble high molecular polymer and mixing evenly, adding polyol and mixing evenly, to obtain a mixed solution of functional main ingredients; (3) adding alkaline solution to adjust the pH of the mixed solution of the functional main ingredients, continuing to stir for a period of time, first adding the crosslinking agent 1 and mixing evenly, adding water, and then adding the solution of the crosslinking agent 2 and mixing evenly; finally adding the surfactant and mixing evenly to obtain the skinning material with the crosslinked network structure.
6. The method for preparing a skinning material with a cross-linked network structure according to claim 5, characterized in that: Step (1), the heating temperature is 90-95°C; In step (2), the heating temperature is 40-55°C.
7. The method for preparing a skinning material with a cross-linked network structure according to claim 5, characterized in that: Step (2), the alginate is added to the water-soluble polymer solution and mixed for 2.5-3.5 hours; The time for adding polyol and mixing evenly is 0.5-1.5 h.
8. The method for preparing a skinning material with a cross-linked network structure according to claim 5, characterized in that: Step (3), The lye is a solution of sodium hydroxide; Adjusting the pH of the mixed solution of the functional main ingredients to 9.5-10.5; Continue stirring for 25-35 min.
9. The method for preparing a skinning material with a cross-linked network structure according to claim 8, characterized in that: Step (3), The alkali solution is a sodium hydroxide solution with a concentration of 0.9-1.2 mol / L; The time for adding the crosslinking agent and mixing evenly is 2.5-3.5 h; Add water to make the volume of the solution 230-260ml; The volume of the solution containing the cross-linking agent 2 is 23-26 ml.
10. Use of a crusting material having a cross-linked network structure as claimed in any one of claims 1 to 4 in dust control.
Citation Information
Patent Citations
Soil conditioner and preparation method thereof
CN115772267A
Self-healing inhibitor for inhibiting spontaneous combustion of coal and application of self-healing inhibitor
CN117624742A
Dual-network reinforced structure dust suppression material and preparation method thereof
CN118374064A